High L21-atomic ordering and spin-polarization in Co2MnZ (Z = Ge, Sn) Heusler thin films with low-temperature annealing process - Varun Kumar Kushwaha; Yuya Sakuraba; Tomoya Nakatani; Taisuke Sasaki; Ivan Kurniawan; Yoshio Miura; Hiroo Tajiri; Kazuhiro Hono (APL Materials, 2022)
Although an enhanced magnetoresistance (MR) has been observed in many Co2-based Heusler alloys by promoting their structural ordering from B2 to L21 by post-annealing at higher temperatures (Tann > 500 °C), it is desirable to search for other Heusler alloys that crystallize in L21-order below 300 °C, as the maximum Tann is restricted for processing devices. For Co2MnZ (Z = Ge, Sn) Heusler alloys, an L21-order is expected to appear even in the as-deposited state or by a low-temperature annealing process due to their very high L21 to B2-order transition temperature (>1500 K). Here, epitaxial Co2MnZ films were grown on MgO (001) substrate at room temperature (RT) and post-annealed at Tann = 200–500 °C. Interestingly, as-sputtered films exhibit L21-ordering, which improves systematically upon increasing Tann. The spin-polarization of electric current (β) was estimated at RT using nonlocal spin-valve (NLSV) devices by measuring the spin-accumulation signal in a copper (Cu) channel. It was found that at Tann = 300 °C, the β value of Co2MnGe films is higher (∼0.65) than that of Co2FeGe0.5Ga0.5 films due to a higher degree of L21-order, which makes the Co2MnGe alloy a promising ferromagnetic electrode for spintronic device applications.